(untitled) (International Journal of Engineering and Computer Science, 2014)
When no transformer is used in a grid-connected photovoltaic (PV) system, a galvanic connection between the grid and the PV array exists. In these conditions, dangerous ground currents (common-mode currents) can appear through the stray capacitance between the PV array and the ground. This current increase conducted and radiated electromagnetic emissions, harmonics injected in the utility grid and losses.In this paper, an improved output filter for reduction of common mode voltage and ground current in a grid connected full bridge(FB) inverter is proposed .A model for measurement of this ground voltage and current is build by using simulation software. Finally ground voltage and current of a FB inverter using conventional LCL filter and proposed filter is measured and compared with satisfactory results.